Буровое оборудование: учебное пособие - Крец В. Г. Виктор Георгиевич; Саруев Л. А. Лев Алексеевич; Лукьянов В. Г. Виктор Григорьевич; Шадрина А. В. Анастасия Викторовна; Шмурыгин В. А. Владимир Александрович; Саруев А. Л. Алексей Львович (Томск, Изд-во ТПУ, 2011)
Заглавие с титульного экрана